Marine algae of the St. Martin's Island, Bangladesh. VI. New records of species of the genus Kallymenia J. Ag. (Rhodophyta) (Bangladesh Journal of Botany, 2008)
Four species of the genus Kallymenia J. Ag. such as K. cribrosa Harvey, K. rosea Womersley & Norris, K. rubra Womersley & Norris K. tasmanica Harvey have been reported for the first time from St. Martin's Island, Bangladesh. Key words: Seaweeds, Marine algae, Kallymenia spp., St. Martin's Is., Bangladesh doi:10.3329/bjb.v37i2.1726 Bangladesh J. Bot. 37(2): 173-178, 2008 (December)